The effects of innovation on firm performance of supporting industries in Hanoi-Vietnam - Nham Tuan; Nguyen Nhan; Pham Giang; Nguyen Ngoc (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: Innovation, including product, process, marketing, and organizational innovation within a firm, is considered as one of essential component for surviving and growing. These innovation activities create value and competitive advantages for successful organizations; therefore, understanding the organization's overall innovation is the first and foremost to understand the role of innovation on firm performance. The objective of this research is to explore two parts: the impacts of innovation on the different aspect of innovation performance, then their effects to firm performance (production, market, and financial performance). Design/methodology/approach: This study uses primary data from questionnaire survey. The questionnaire involves 4 parts including general information, innovation activities; innovative performance, and firm performance. This research focuses on firms in supporting industries of mechanics, electronics, motorbike and automobile. These firms are in a list of companies (known as The Excellent Vietnamese Companies in Northern and Central Vietnam) established by JETRO and VCCI. There are 150 firms in this list. The questionnaire survey was administered to directors, CEO of those firms during April and May, 2014. Out of the 150 questionnaires sent out, 118 were valid, accounting for 78.7% of the true response rate. Analysis methodologies of reliability, factor analysis and regression are utilized in this paper. Findings: The result demonstrated there are positive effects of process, marketing, and organizational innovations on firm performance in supporting firms. More specifically, the higher the level of innovation activities is, the greater the innovative performance is, which means the larger level of Process, organization and marketing innovation activities are, the higher level of innovative performance are likely to be. Secondly, the higher level of Process, organization and marketing innovative performance, the better level of firm performances is likely to be. To sum up, in order to improve the innovative and firm performance, those firms in supporting industry should highly concentrate on process, marketing, and organizational innovation activities, rather than product innovation activities. Originality/value: Initially, this study applies successfully the model which supposing innovation is a process, then clarifying innovation definition through the impact of innovation activities on innovative performances. Secondly, this research confirmed the positive impact of innovative performances on firm performances. It provided one more empirical evidence of the relationship between innovation and firm performance. For practitioners, organizational innovation and process innovation are more important factors affecting innovative performance and firm performance than product and marketing innovation. Therefore, enterprises should focus and mobilize resources to create improvement in organizational structure and manufacturing processes.
Keywords: 650; innovation; manufacturing firm; innovative performance; firm performance